Past-time marker –ed in the speech and written work of Indonesian English majors - Mohammad Lotfie, Maskanah; Wulandari, Diyah Fitri; Nurhamidah, Idha (English Language Education Journals, 2017)
This paper presents a descriptive investigation on verbal and written use of past-time inflectional marker -ed by Indonesian English majors. Given that English has a foreign language status in Indonesia, acquiring grammatical forms and specific to this study, the –ed inflection, is challenging to learners. Difficulties in acquiring the form is amplified by cross-linguistic influence as the majority of EFL learners in Indonesia speak Javanese as their first language and Indonesian as the second, while exposure to English and to this study’s temporal target form is minimal. The salience of –ed and its allomorphs plays a part in determining the learners usage of the form, with syllabic forms predicted to be perceptually more prominent and easier to acquire. Thirty undergraduates who were English Literature and English Education majors in Central Java participated in this study. Due to the two-fold nature of the investigation, data were collated using two instruments; one elicited written usage of the target form while the other stimulated the participants’ verbal output. Although there were missing –ed inflections where obligatory, results suggest students’ ease and considerable consistency in using the written form of the –ed temporal marker. On the contrary, the English majors generally used the default form of the regular verbs when -ed allomorphs [t], [d] and [ɪd] were required in their speech. To a certain extent, cross-linguistic influence and saliency are relevant in discussing the acquisition of the forms. Instructional intervention should help the English majors and others comparable them, whose closer approximation to Standard English is very important, in completing their university academic programmes as well as in enhancing chances of employability which includes teaching English.